Preparation method of nitrogen self-doped magnetic porous biochar

By using pepper branches and pepper seed raw materials, combined with cellulase pretreatment and composite activator carbonization treatment, nitrogen self-doped magnetic porous biochar was prepared, which solved the problems of poor adsorption performance and low recovery of existing biochar, and achieved efficient adsorption and stable reuse.

CN119869457APending Publication Date: 2025-04-25CHONGQING UNIV OF ARTS & SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510253435.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing nitrogen-doped magnetic biochar has a small specific surface area and poor adsorption performance, which limits its practical application, especially in terms of recycling and reusing and stability of adsorption performance.

Method used

Pepper branches and pepper seeds are used as raw materials, and after pretreatment by cellulase, combined with potassium iron perate and potassium oxalate as composite activators, step-by-step high-temperature carbonization is carried out to form nitrogen self-doped magnetic porous biochar.

Benefits of technology

It significantly improves the specific surface area and adsorption performance of biochar, has excellent adsorption effect on organic dyes such as methylene blue, lemon yellow and carmine red, and improves negative magnetic properties, achieving high recovery and adsorption stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869457A_ABST
    Figure CN119869457A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of nitrogen self-doped magnetic porous biochar, which comprises the following steps: by taking pepper branches as a raw material, carrying out pretreatment treatment, and then carrying out step-by-step high-temperature carbonization treatment by taking ferric potassium permanganate and ferric potassium oxalate as a composite activating agent, namely mixing pepper branch powder, cellulase and water, and carrying out constant-temperature reaction at 50-60 DEG C for 12-16 hours, so as to obtain the nitrogen self-doped magnetic porous biochar. After the reaction is finished, filtering to obtain a solid sample, washing the solid sample to be neutral, and then drying to obtain pretreated raw material powder; the biochar prepared through cellulase pretreatment and K2FeO4 and K3 [Fe (C2O4) 3 composite activation treatment has an excellent specific surface area and a specific void structure, has excellent adsorption performance on organic dyes such as methylene blue, lemon yellow and carmine, effectively improves the negative magnetic performance of the biochar, and is high in recovery rate and recovery rate. And the subsequent biochar keeps excellent adsorption stability in the repeated use process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biochar preparation, and in particular to a method for preparing nitrogen self-doped magnetic porous biochar. Background Art

[0002] Porous carbon materials have controllable pore structures and surface chemical properties, and are widely used in catalysis, adsorption separation, sensing, electrochemistry and other fields. The properties of porous carbon materials can be further improved by modification, doping and other methods, thereby enhancing their application value. Nitrogen is an ideal element for doping carbon materials, and nitrogen doping can effectively improve the physical and chemical properties of carbon materials. The atomic radius of single atoms and carbon atoms is similar, so it is easier to replace carbon atoms in the atomic lattice of carbon materials, thereby forming doping. Nitrogen atoms have one more extranuclear electron than carbon atoms and have a high electron affinity, so that the carbon atoms adjacent to the N heteroatom in the nitrogen-doped carbon material have a high positive charge density. At the same time, there is a conjugation effect between the lone pair of electrons of the N atom and the large π bond of the carbon atom lattice (nitrogen doping changes the charge distribution of porous carbon and increases the number of defective carbon sites, thereby enhancing the adsorption capacity of pollutants. Nitrogen doping introduces nitrogen-containing functional groups and improves the surface hydrophilicity of carbon materials), so that nitrogen-doped carbon materials exhibit excellent electrochemical and catalytic properties. Studies have reported that nitrogen doping changes the electronic structure of carbon, increasing the charge carrier density and quantum capacitance, leading to greater interfacial capacitance. There are three main ways to dope carbon: (1) using nitrogen-rich monomers as precursors in nanocasting and soft template methods; (2) using nitrogen-containing biomass as precursors; and (3) post-treating carbon with nitrogen sources such as ammonia or urea at high temperatures.

[0003] Waste Zanthoxylum bungeanum is rich in nitrogen and is a high-quality raw material for preparing nitrogen self-doped carbon materials. Therefore, using Zanthoxylum bungeanum branches as nitrogen-containing biomass raw materials, nitrogen-doped carbon materials can be obtained through simple carbonization treatment. As an adsorption material, in addition to considering the adsorption performance of carbon materials, the recovery and reuse of carbon materials must also be considered. In the prior art, the carbon materials are negatively magnetized and the reuse of carbon materials is achieved through magnetic separation technology. Nitrogen-doped magnetic biochar is generally prepared in two ways. One is to first carbonize the biomass raw material and the nitrogen source to prepare nitrogen-doped biochar, and then load the magnetism through iron salts. The other is to mix the raw material, nitrogen source and iron salt and carbonize them. However, the materials obtained by the above methods have problems such as small specific surface area and poor adsorption performance, which limits practical applications. Summary of the invention

[0004] Based on the above problems, the purpose of the present invention is to provide a method for preparing nitrogen self-doped magnetic porous biochar, which is prepared using Zanthoxylum bungeanum branches and Zanthoxylum bungeanum seeds as raw materials.

[0005] Nitrogen doping can introduce defects and improve the physical and chemical properties of the catalyst. The purpose of the present invention is achieved through the following technical solutions: A method for preparing nitrogen self-doped magnetic porous biochar is characterized in that: pepper branches are used as raw materials, after pretreatment, potassium peroxide iron and potassium iron oxalate are used as composite activators, and high-temperature carbonization treatment is performed in steps.

[0006] Furthermore, the pretreatment is to add cellulase and water to the Zanthoxylum bungeanum branch powder, mix them evenly, and then react them at a constant temperature of 50-60°C for 12-16 hours. After the reaction is completed, filter out the solid sample, wash the solid sample to neutrality, and then dry it.

[0007] Furthermore, the dosage ratio of the Zanthoxylum bungeanum branch powder, cellulase and water is 10g:0.1-0.3g:50mL, and the cellulase activity is 500-1000U / g.

[0008] Furthermore, the composite activator is composed of potassium peroxide iron and potassium iron oxalate in a mass ratio of 5-6:1, and the mass ratio of the raw material to the composite activator is 1:0.25-2.

[0009] Furthermore, the step-by-step high-temperature carbonization treatment is to treat the mixture at 300-450° C. for 0.5-1 h, and then at 700-800° C. for 0.5-1 h in an inert gas atmosphere.

[0010] Since the nitrogen content in Zanthoxylum bungeanum branches is high, using it as a raw material to prepare carbon materials will obtain highly nitrogen-doped activated carbon, which is beneficial to improve the adsorption performance of carbon materials. However, it was found in the negative magnetic process that the negative magnetic effect was very poor, making it difficult to recycle the activated carbon, with a low recovery rate, and the adsorption performance of the recycled carbon materials was seriously reduced during reuse.

[0011] In the present invention, the pepper branches are first pretreated with cellulase, and the pretreated pepper branches are mixed with a composite activator composed of potassium peroxide and potassium iron oxalate in a specific ratio, and then carbonized at high temperature. During the pretreatment process, the cellulase initially degrades the pepper branches, changing the structure of the lignocellulose in the pepper branches, and then mixed with the composite activator and deionized water, and the potassium peroxide is decomposed into Fe(OH)3 and KOH. During the carbonization process, as the temperature gradually increases, within the pyrolysis temperature range of 300-400°C and in the carbon material environment of the pepper branches, Fe(OH)3 is converted into Fe3O4, Fe2O3, etc., and potassium iron oxalate is decomposed into iron oxide and K2CO3 at a pyrolysis temperature of 300-450°C. A small amount of carbon is consumed in this process. The formation of preliminary pores is conducive to the entry of major components such as KOH and K2CO3 into the vicinity of the preliminary formed pores. As the temperature rises to 700-800°C, KOH and K2CO3 synergistically activate pores based on the preliminary formed pores, forming a rich pore structure while achieving the purpose of synchronous negative magnetism. The potassium vapor generated in this process shuttles through the pores while increasing the distance between carbon atom layers, promoting the migration of iron and iron oxides in the carbon material, thereby achieving the effect of uniform loading. The uniform loading of magnetic particles is conducive to the recovery and reuse of biochar.

[0012] Most specifically, a method for preparing nitrogen self-doped magnetic porous biochar is characterized by comprising the following steps: (1) Take the pepper branch and dry it, then crush it with a grinder, pass it through a 60-100 mesh sieve to obtain the pepper branch powder, and pretreat the pepper branch powder by mixing the pepper branch powder, cellulase and water, and reacting it at a constant temperature of 50-60°C for 12-16 hours. After the reaction is completed, filter to obtain a solid sample, wash the solid sample to neutrality, and then dry it. The dosage ratio of pepper branch powder, cellulase and water is 10g:0.1-0.3g:50mL, and the cellulase activity is 500-1000U / g; (2) Mixing the pretreated Zanthoxylum bungeanum powder, a composite activator and deionized water, stirring for 4 to 8 hours, and then drying, wherein the composite activator is composed of potassium peroxide iron and potassium iron oxalate in a mass ratio of 5 to 6:1, and the pretreated Zanthoxylum bungeanum powder, the composite activator and deionized water in a mass ratio of 1 g:0.25 to 2 g:50 mL; (3) The mixture was heated to 300-450°C at a rate of 2-5°C / min under an inert gas atmosphere and treated for 0.5-1h, and then heated to 700-800°C at a rate of 5-10°C / min and treated for 0.5-1h. The carbonized material was ground and washed with ultrapure water, separated by a magnet, and dried at 60°C to obtain nitrogen self-doped magnetic porous biochar.

[0013] The present invention has the following technical effects: The biochar prepared by the present invention through cellulase pretreatment and then composite activation treatment with K2FeO4 and K3[Fe(C2O4)3 has excellent specific surface area and specific void structure, and has excellent adsorption performance for organic dyes such as methylene blue, lemon yellow and carmine. At the same time, the negative magnetic properties of the biochar are effectively improved, the recovery rate is fast, the recovery rate is high, and the biochar after the treatment maintains excellent adsorption stability during repeated use. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 : Scanning electron micrograph of the biochar prepared in Example 1 of the present invention.

[0015] Figure 2 : Adsorption performance diagram of lemon yellow after repeated adsorption and recovery 10 times by biochar prepared in Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0016] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.

[0017] Example 1 A method for preparing nitrogen self-doped magnetic porous biochar comprises the following steps: (1) Take the pepper branch and dry it, then crush it with a grinder, pass it through a 60-100 mesh sieve to obtain the pepper branch powder, and pretreat the pepper branch powder by mixing the pepper branch powder, cellulase and water, and reacting them at a constant temperature of 55°C for 14 hours. After the reaction is completed, filter to obtain a solid sample, wash the solid sample to neutrality, and then dry it. The dosage ratio of pepper branch powder, cellulase and water is 10g:0.2g:50 mL, and the cellulase activity is 1000U / g; (2) mixing the pretreated Zanthoxylum bungeanum powder, a composite activator and deionized water, stirring for 5 hours, and then drying, wherein the composite activator is composed of potassium peroxide iron and potassium iron oxalate in a mass ratio of 5.5:1, and the pretreated Zanthoxylum bungeanum powder, the composite activator and deionized water in a mass ratio of 1 g:1 g:50 mL; (3) The mixture was heated to 400 °C at a rate of 4 °C / min under an inert gas atmosphere for 1 h, and then heated to 750 °C at a rate of 8 °C / min for 1 h. The carbonized material was ground and washed with ultrapure water. After separation with a magnet, it was dried at 60 °C to obtain nitrogen self-doped magnetic porous biochar.

[0018] Comparative Example 1 The difference from Example 1 is that the choice of activator is different. During the preparation process, different activators are tried to treat the raw materials. Specifically, single ZnCl2, K2FeO4, K3[Fe(C2O4)3 are used as activators for addition treatment, and ZnCl2 is used to replace K2FeO4 and K3[Fe(C2O4)3 in Example 1 respectively. The remaining steps are the same as in Example 1, and the addition amount is the optimal addition amount corresponding to each activator.

[0019] Comparative Example 2 The difference from Example 2 is that during the preparation process, no pretreatment is performed, and the Zanthoxylum bungeanum branch raw material powder is directly mixed and stirred with the composite activator and deionized water, and the carbonization step is the same as that of Example 1. The effects of pretreatment steps and different activating agent treatments on the physical properties of the prepared biochar are shown in Table 1.

[0020] Table 1:

[0021] It can be seen that the specific surface area of ​​the Zanthoxylum branch-based biochar treated with different activators and the distribution of the formed pores are quite different. After cellulase pretreatment and then treated with a single activator, the biochar prepared by the ZnCl2 group has a larger specific surface area and a higher total pore volume than that of the other groups. In the two-by-two composite process, the specific surface area and total pore volume of the biochar treated with the composite of ZnCl2 and K2FeO4 are significantly improved, while the specific surface area of ​​the biochar treated with the composite of ZnCl2 and K3[Fe(C2O4)3 is significantly reduced. In Example 1 of the present invention, the specific surface area of ​​the biochar is significantly improved by the composite treatment of K2FeO4 and K3[Fe(C2O4)3, and the total pore volume is also significantly increased. When no cellulase pretreatment is performed, the specific surface area is significantly reduced compared with Example 1, and the total pore volume is also reduced, but it is still better than other single activator treatment groups.

[0022] Verification of adsorption performance: The adsorption effect of biochar on methylene blue, lemon yellow and carmine was investigated and verified. In the adsorption test, the adsorbate concentration was 500 mg / L, 100 mg of biochar was added to 100 mL, and the adsorption amount of the adsorbate was calculated after the adsorption reaction was completed at an appropriate pH and room temperature. The results are shown in Table 2.

[0023] Table 2:

[0024] As can be seen from the above table, the biochar prepared in Example 1 of the present invention has excellent adsorption and removal effects on methylene blue, lemon yellow and carmine, with removal rates reaching more than 90%, and the adsorption equilibrium time is shorter than that of single K2FeO4 and K3[Fe(C2O4)3. Compared with Example 1, in addition to the decrease in adsorption performance, the adsorption equilibrium time of methylene blue and carmine in Comparative Example 2 is also prolonged.

[0025] Biochar magnetic verification: After the adsorption was completed, the biochar in the solution was recovered by magnetic adsorption, and the recovery rate within 2 min of recovery time was calculated, as shown in Table 3.

[0026] Table 3:

[0027] As can be seen from the above table, in the negative magnetic process, the Fe content of biochar prepared by single K2FeO4 and K3[Fe(C2O4)3 treatment is not high, and there is a significant difference in the proportion of Fe3O4, resulting in poor recovery of subsequent biochar. The total Fe content in biochar treated with ZnCl2+ K2FeO4 and ZnCl2+ K3[Fe(C2O4)3 is higher than that of single K2FeO4 and K3[Fe(C2O4)3, but the proportion of Fe3O4 is low, resulting in a lower recovery rate than that of single K2FeO4 and K3[Fe(C2O4)3 treatment groups. In Example 1, the biochar treated with K2FeO4+K3[Fe(C2O4)3 had a significantly increased total Fe content, a higher Fe3O4 ratio, and a biochar recovery rate of 98.4%. In Comparative Example 2, cellulose was not used for pretreatment, and although the total Fe content was significantly increased compared to the single K2FeO4 and K3[Fe(C2O4)3 treatments, it was significantly lower than that in Example 1, and the Fe3O4 ratio was also significantly decreased compared to Example 1, resulting in a significant decrease in the biochar recovery rate.

[0028] The magnetic particles in the biochar prepared in Example 1 of the present invention enhance the recovery and separation efficiency of the biochar, and promote the recycling of the biochar. After adsorbing methylene blue, lemon yellow and carmine and repeating the adsorption 10 times, the removal rate of the biochar for each organic dye is still maintained at 95% of the first removal rate. The nitrogen self-doped magnetic porous biochar prepared by the present invention has excellent adsorption stability and can be reused many times without performance attenuation.

[0029] Example 2 A method for preparing nitrogen self-doped magnetic porous biochar comprises the following steps: (1) Take the pepper branch and dry it, then crush it with a grinder, pass it through a 60-100 mesh sieve to obtain the pepper branch powder, and pretreat the pepper branch powder by mixing the pepper branch powder, cellulase and water, and reacting them at a constant temperature of 60°C for 12 hours. After the reaction is completed, filter to obtain a solid sample, wash the solid sample to neutrality, and then dry it. The dosage ratio of pepper branch powder, cellulase and water is 10g:0.1g:50mL, and the cellulase activity is 500U / g; (2) Mixing the pretreated Zanthoxylum bungeanum powder, a composite activator and deionized water, stirring for 4 hours, and then drying, wherein the composite activator is composed of potassium peroxide iron and potassium iron oxalate in a mass ratio of 6:1, and the pretreated Zanthoxylum bungeanum powder, the composite activator and deionized water in a mass ratio of 1 g:0.25 g:50 mL; (3) The mixture was heated to 450°C at a rate of 2°C / min under an inert gas atmosphere and treated for 0.5 h, and then heated to 700°C at a rate of 10°C / min and treated for 1 h. After the carbonization, the material was ground and washed with ultrapure water, separated by a magnet, and dried at 60°C to obtain nitrogen-doped magnetic porous biochar.

[0030] The nitrogen self-doped magnetic porous biochar prepared in this embodiment has an adsorption capacity of 485 mg / g, 470 mg / g and 494 mg / g for methylene blue, tartrazine and carmine, and the recovery rate of biochar reaches 98.8% within 2 minutes. It can be reused more than 10 times, and the removal rates of methylene blue, tartrazine and carmine are all stable at more than 94% of the first time.

[0031] Example 3 A method for preparing nitrogen self-doped magnetic porous biochar comprises the following steps: (1) Take the pepper branch and dry it, then crush it with a grinder, pass it through a 60-100 mesh sieve to obtain the pepper branch powder, and pretreat the pepper branch powder by mixing the pepper branch powder, cellulase and water, and reacting it at a constant temperature of 50-60°C for 12-16 hours. After the reaction is completed, filter to obtain a solid sample, wash the solid sample to neutrality, and then dry it. The dosage ratio of pepper branch powder, cellulase and water is 10g:0.3g:50mL, and the cellulase activity is 1000U / g; (2) Mixing the pretreated Zanthoxylum bungeanum powder, a composite activator and deionized water, stirring for 8 h, and then drying, wherein the composite activator is composed of potassium peroxide iron and potassium iron oxalate in a mass ratio of 5:1, and the pretreated Zanthoxylum bungeanum powder, the composite activator and deionized water in a mass ratio of 1 g: 2 g: 50 mL; (3) The mixture was heated to 300 °C at a rate of 5 °C / min under an inert gas atmosphere for 1 h, and then heated to 800 °C at a rate of 5 °C / min for 0.5 h. The carbonized material was ground and washed with ultrapure water. After separation with a magnet, it was dried at 60 °C to obtain nitrogen self-doped magnetic porous biochar.

[0032] The nitrogen self-doped magnetic porous biochar prepared in this embodiment has an adsorption capacity of 488 mg / g, 461 mg / g and 482 mg / g for methylene blue, tartrazine and carmine, and the recovery rate of biochar reaches 98.8% within 2 minutes. It can be reused more than 10 times, and the removal rates of methylene blue, tartrazine and carmine are all stable at more than 93% of the first time.

Claims

1. A method for preparing nitrogen self-doped magnetic porous biochar, characterized in that: The Zanthoxylum bungeanum branches are used as raw materials, and after pretreatment, potassium peroxide iron and potassium iron oxalate are used as composite activators, and subjected to step-by-step high-temperature carbonization treatment. The pretreatment is to mix Zanthoxylum bungeanum branch powder, cellulase and water, and react at a constant temperature of 50-60°C for 12-16 hours. After the reaction is completed, a solid sample is filtered to obtain a solid sample, and the solid sample is washed to neutrality and then dried to obtain a pretreated raw material powder.

2. The method for preparing nitrogen self-doped magnetic porous biochar according to claim 1, characterized in that: The dosage ratio of the Zanthoxylum bungeanum branch powder, cellulase and water is 10g:0.1-0.3g:50mL.

3. The method for preparing nitrogen self-doped magnetic porous biochar according to claim 1 or 2, characterized in that: The composite activator is composed of potassium peroxide iron and potassium iron oxalate in a mass ratio of 5-6:1, and the raw material and the composite activator in a mass ratio of 1:0.25-2.

4. A method for preparing nitrogen self-doped magnetic porous biochar according to any one of claims 1 to 3, characterized in that: The step-by-step high-temperature carbonization treatment is to treat the mixture at 300-450° C. for 0.5-1 h, and then at 700-800° C. for 0.5-1 h in an inert gas atmosphere.

5. A method for preparing nitrogen self-doped magnetic porous biochar, characterized in that: The steps include: (1) Taking pepper branches and drying them, and then crushing them with a grinder, passing them through a 60-100 mesh sieve to obtain pepper branch powder, and pretreating the pepper branch powder, specifically, mixing the pepper branch powder, cellulase and water, and reacting them at a constant temperature of 50-60° C. for 12-16 hours. After the reaction is completed, filtering to obtain a solid sample, washing the solid sample to neutrality, and then drying it, the dosage ratio of pepper branch powder, cellulase and water is 10 g: 0.1-0.3 g: 50 mL, and the cellulase activity is 500-1000 U / g; (2) Mixing the pretreated Zanthoxylum bungeanum powder, a composite activator and deionized water, stirring for 4 to 8 hours, and then drying, wherein the composite activator is composed of potassium peroxide iron and potassium iron oxalate in a mass ratio of 5 to 6:1, and the pretreated Zanthoxylum bungeanum powder, the composite activator and deionized water in a mass ratio of 1 g:0.25 to 2 g:50 mL; (3) The mixture was heated to 300-450°C at a rate of 2-5°C / min under an inert gas atmosphere and treated for 0.5-1 h. Then, the mixture was heated to 700-800°C at a rate of 5-10°C / min and treated for 0.5-1 h. After the carbonization, the material was ground and washed with ultrapure water. After separation with a magnet, it was dried at 60°C to obtain nitrogen self-doped magnetic porous biochar.